Promoting Halal Tourism through Cultural Heritage: The Impact of the “One Nagari, One Event” Program on Tourist Intentions - Rahmat, Rahmat; Rakotoarisoa Maminirina Fenitra; Haura Hazimah Melzatia (Journal of Digital Marketing and Halal Industry, 2025)
The “One Nagari, One Event” program is an initiative by the Tanah Datar Regency Government aimed at preserving culture and traditions, promoting tourism potential, and improving the local economy. This program has had a significant impact on Tanah Datar Regency. Existing studies in this context primarily examine the influence of variables such as attitudes, subjective norms, behavioral control, and facilities on tourists’ intentions to visit Tanah Datar Regency. This research seeks to answer the question: how do the variables of attitude, subjective norms, behavioral control, and facilities influence tourists’ intention to visit Tanah Datar Regency? To address this question, a quantitative approach was employed to analyze the effect of these variables on tourists’ visiting intentions. The findings reveal that attitudes, subjective norms, behavioral control, and facilities have a positive and significant influence on tourists’ intention to visit Tanah Datar Regency. However, the results show that the variable of promotion, while positively correlated, does not significantly influence tourists’ visiting intentions. This study also highlights the importance of improving event quality and building strong branding to achieve optimal visitor numbers.